Modelo de contrato EPC - Engineering, Procuremenet and Construction - como instrumento de redução de riscos e custos em Project Finance de geração de energia Hidrelétrica no Brasil - Ribeiro Filho, Valfredo de Assis (2008)
The current model in the Institutional Electrical Sector, due to criteria for granting concessions and authorizations, has encouraged the implementation of energy production projects through project financing by negotiating EPC (Engineering, Procurement and Construction) Turnkey Lump Sum Agreements. An incomplete or poorly prepared EPC Agreement increases the entrepreneur s risk of being exposed to price and deadline increases. Another characteristic of this contracting modality is the long time that the entrepreneur and contractor take to close an agreement, which results in significant cost. In this context, the purpose of this paper is to conduct a study of all aspects involving the preparation of an EPC Agreement, with a proposal at the end as a consequence and supplement to the study, an EPC Agreement for Hydroelectric Plants (UHE s) in Brazil, in order for the entrepreneur to reduce risks and costs. The study conducted involved regulatory aspects associated with bids for concessions, a study of the project finance literature and the actual EPC Agreement, an economic approach to the asymmetry of information, as well as an assessment of the legal aspects under Brazilian laws. As a supplement to the study, for the incorporation of practical experience into the work, a survey was conducted on EPC agreements for UHE s entered into in Brazil in the last ten years and an analysis of the EPC Agreement model internationally accepted and proposed by the FIDIC (International Federation of Consulting Engineers). As a result of the study and research conducted a detailed analysis was presented of the EPC contracting modality, including an individual discussion of each of the contract clauses. At the end a proposal was made for an EPC Agreement model for UHE s in Brazil. The construction of this model aimed to overcome several recurring imperfections and equivocations identified in the study and research phases, such as: lack of logical order to the clauses; excessive remissions; multiplicity of attachments; confusion in the order of prevalence among the documents in the agreement; and equivocated translations with terms in English. In addition, the model takes into account several precautions normally absent in most EPC agreements, such as a well-balanced sharing of risks by the parties, particularly in relation to geological risks, with reference to the provisions in the Brazilian Civil Code that protect the contractor (excessive financial burden and theory of unpredictability.) The use of this model gives the entrepreneur more security when adopting a complete, correct and well-balanced EPC agreement, that is, one that contains all of the provisions necessary to characterize an EPC model that correctly governs all of the situations and has a well-balanced sharing of risks in order to actually serve as a model to be used a standard. Adopting this model also enables a significant reduction in timeframes to negotiate the agreement between entrepreneurs and contractors, resulting in a significant reduction in transaction costs.